Advancements in Osteosarcoma Therapy: Overcoming Chemotherapy Resistance and Exploring Novel Pharmacological Strategies - Mahmoud Zhra; Shahid Akhtar Akhund; Khalid S. Mohammad (Pharmaceuticals)
Osteosarcoma is recognized as the most prevalent primary bone malignancy, primarily affecting children and adolescents. It is characterized by its aggressive behavior and high metastatic potential, which often leads to poor patient outcomes. Despite advancements in surgical techniques and chemotherapy regimens, the prognosis for patients with osteosarcoma remains unsatisfactory, with survival rates plateauing over the past few decades. A significant barrier to effective treatment is the development of chemotherapy resistance, which complicates the management of the disease and contributes to high rates of recurrence. This review article aims to provide a comprehensive overview of recent advancements in osteosarcoma therapy, particularly in overcoming chemotherapy resistance. We begin by discussing the current standard treatment modalities, including surgical resection and conventional chemotherapy agents such as methotrexate, doxorubicin, and cisplatin. While these approaches have been foundational in managing osteosarcoma, they are often limited by adverse effects and variability in efficacy among patients. To address these challenges, we explore novel pharmacological strategies that aim to enhance treatment outcomes. This includes targeted therapies focusing on specific molecular alterations in osteosarcoma cells and immunotherapeutic approaches designed to harness the body’s immune system against tumors. Additionally, we review innovative drug delivery systems that aim to improve the bioavailability and efficacy of existing treatments while minimizing toxicity. The review also assesses the mechanisms underlying chemotherapy resistance, such as drug efflux mechanisms, altered metabolism, and enhanced DNA repair pathways. By synthesizing current research findings, we aim to highlight the potential of new therapeutic agents and strategies for overcoming these resistance mechanisms. Ultimately, this article seeks to inform future research directions and clinical practices, underscoring the need for continued innovation in treating osteosarcoma to improve patient outcomes and survival rates.